"It's a Concrete Ceiling; It's Not Even Glass": Understanding Tenets of Organizational Culture That Supports the Progression of Women as Coaches and Coach Developers. (October 2018) - Norman, Leanne; Rankin-Wright, Alexandra J.; Allison, Wayne
The purpose of this study was to explore what particular areas of organizational cultures facilitate the development and progression of women as football coaches and coach developers. The English Football Association provided the context for the research. Previous statistics demonstrate that recruitment, retention, and progression of women in English football coaching and tutoring are lower and slower than their male counterparts. In-depth interviews were completed with 26 women coaches and coach developers during November 2015 and February 2016 to understand their personal experiences as linked to the structure and culture of their sporting governing body, and analyzed using Schein's theory of organizational culture. Three key tenets of organizational culture were found to be most influential on the career development of the participants: journeys and crossroads (the establishment of a learning culture), inclusive leadership, and vertical and horizontal relationships. The research demonstrates the need to identify disparities between espoused values and assumptions to enact cultural change toward supporting more women to be valued, included, and progressed in the sporting workplace.